Quinoa protein Pickering emulsion: A promising cryoprotectant to enhance the freeze-thaw stability of fish myofibril gels. (1st May 2023) - Cen, Kaiyue; Huang, Caoxing; Yu, Xi; Gao, Chengcheng; Yang, Yuling; Tang, Xiaozhi; Feng, Xiao
Graphical abstract: Highlights: Quinoa protein Pickering emulsion (QPE) reduced the ice crystal size in fish protein gel. QPE addition decreased the freezing point of fish myofibrillar protein (MP) gels. QPE enhanced the juiciness and gel strength of MP gels after freeze–thaw (F-T) cycles. QPE addition retarded the protein oxidation in fish MP gels after F-T cycles. QPE stabilized water distribution and tertiary structure of MP gels after F-T cycles. Abstract: In this work, the effects of different QPE addition on the freeze–thaw (F-T) stability of fish myofibrillar protein (MP) gels were revealed. During freezing process, QPE decreased the freezing point of MP gels and shortened the time to pass through the maximum-ice-crystal-formation zone. The occurrence of thermal hysteresis effect led to the formation of small ice crystals and alleviated the damage to MP gel network. The incorporation of 7.5% QPE also reduced the free water amount to 19.23% and improved the water holding capacity of MP gels. Furthermore, the incorporation of QPE decreased the carbonyl content of MP gels after F-T cycles and delayed the protein oxidation. Meanwhile, QPE addition maintained the stability of the tertiary structure of MP gels via stabilizing the microenvironment of tyrosine and tryptophan. Overall, QPE shows the potential as a new cryoprotectant to improve the F-T stability of MP gel products.